European Resuscitation Council Guidelines 2021: Paediatric Life Support. (April 2021) - Van de Voorde, Patrick; Turner, Nigel M.; Djakow, Jana; de Lucas, Nieves; Martinez-Mejias, Abel; Biarent, Dominique; Bingham, Robert; Brissaud, Olivier; Hoffmann, Florian; Johannesdottir, Groa Bjork; Lauritsen, Torsten; Maconochie, Ian
Abstract: These European Resuscitation Council Paediatric Life Support (PLS) guidelines, are based on the 2020 International Consensus on Cardiopulmonary Resuscitation Science with Treatment Recommendations. This section provides guidelines on the management of critically ill infants and children, before, during and after cardiac arrest.